CT-optimized skin stroking delivered by hand or robot is comparable - Triscoli, Chantal; Olausson, Håkan; Sailer, Uta; Ignell, Hanna; Croy, Ilona (Frontiers in Behavioral Neuroscience, 2013)
Introduction: The aim of our study was to investigate whether a pleasant tactile stimulation which is manually produced is qualitatively comparable to an analogous tactile stimulation produced instead by a mechanical source. Methods: Thirty-one subjects [16 men, 15 women, 24.5 ± 2.6 years, mean, and standard deviation (SD)] were tested under four different conditions in a repeated measurements design. A pleasant caress-like brush stroke on the hairy skin of the forearm was either produced by a robot or by hand with three different velocities (0.3, 3, and 30 cm/s). In two conditions the subjects were informed about the stroke's source, whereas in two different conditions they were not. Subsequent to the stimulation, the subjects were asked to rate both pleasantness and intensity of each tactile sensation. Results: Consistently, pleasantness ratings were very similar in both conditions. This was found across stimulus velocities and regardless of whether the subjects were informed about the source of the on-going stroke or not. In contrast, intensity ratings were significantly higher in the handheld condition for the two slower velocities, but not for the fastest one. Conclusion: As robot and human touch are highly comparable in terms of perceived pleasantness, handheld stimulation may be used in studies of touch hedonia where robot stimulation is not applicable (for instance in children or certain body parts).